Inpatient mortality in transition-aged youth with rheumatic disease: an analysis of the National Inpatient Sample - Paul T. Jensen; Keumseok Koh; Rebecca E. Cash; Stacy P. Ardoin; Ayaz Hyder (Pediatric Rheumatology Online Journal, 2020)
Abstract Background Transition from pediatric to adult care is a vulnerable time for youth with chronic diseases. In youth with rheumatic disease, studies show high rates of loss to follow up and increased disease activity. However, mortality data are lacking. In this study, we assessed whether transitional age is a risk factor for inpatient mortality. Methods We analyzed the 2012–2014 National Inpatient Sample database, a representative sample of discharges in the United States. Individuals with rheumatic diseases were identified by International Statistical Classification of Disease – 9 (ICD-9) codes at time of discharge. Youth were categorized into three age groups: pre-transitional (11–17), transitional (18–24) and post transitional (25–31). We fitted univariable and multivariable logistic regression models to assess whether transitional age was a risk factor for inpatient mortality. Results There were 30,269 hospital discharges which met our inclusion criteria of diagnosis and age. There were 195 inpatient deaths (0.7%). The most common causes of death were infection (39.5%), pulmonary disease (13.8%), and cardiac disease (11.2%). The Odds ratio for inpatient mortality of a transitional-aged individual was 1.18 compared to controls (p = 0.3). Black race (OR = 1.4), male sex (OR = 1.75), and a diagnosis of systemic sclerosis (OR = 4.81) or vasculitis (OR = 2.85) were the greatest risk factors of inpatient mortality. Conclusion Transitional age was not a risk factor for inpatient mortality in this study. We did identify other risk factors other than age. Further studies are required to assess if there is an increased risk of mortality in outpatients of the transitional age group.